Metabolic Bone Disease of Prematurity: Diagnosis and Management - Faienza, Maria Felicia; D'Amato, Elena; Natale, Maria Pia; Grano, Maria; Chiarito, Mariangela; Brunetti, Giacomina; D'Amato, Gabriele (Frontiers in Pediatrics, 2019)
Metabolic Bone Disease (MBD) of prematurity is a multifactorial condition most common in very low birth weight (VLBW) and extremely low birth weight (ELBW) newborns, characterized by biochemical and radiological findings related to bone demineralization. Several antenatal and postnatal risk factors have been associated to MBD of prematurity, although the main pathogenetic mechanism is the reduced placental transfer of calcium and phosphate due to preterm birth. The diagnosis of MBD of prematurity is based on the evaluation of more biochemical markers and radiological and ultrasonography findings. However, the best approach is the prevention of the symptomatic disease, based on the screening of subjects at risk to develop MBD. The aims of this review were: 1. to summarize the subjects at risk for MBD of prematurity; 2. to indicate the biochemical findings to take in consideration for the prevention of MBD of prematurity; 3. to suggest practical recommendations on nutritional intake and supplementation in these subjects. We searched for papers which reported the current recommendations for biochemical assessment of MBD of prematurity and for the prevention and treatment. Regarding the subjects who need to be screened there is an agreement on the potential risk factors. Different recommendations regard the optimal intake by total parenteral nutrition and enteral feeding. The most of authors suggest that MBD of prematurity is a self limiting disease, thus it is not mandatory to mimic the rate of mineral fetal accretion through parenteral or enteral supplementation. The optimization of total parenteral nutrition (TPN) and the reduction of the duration of TPN, the success of an early achievement of a full enteral feeding are important objectives for the prevention ad management of MBD of prematurity.